Editorial - Chacón Alvarado, Lucía (2001)
This bulletin volume library and the next intended service of the united nations the means of inspiration to propose ideas that offer a community-librarian adaptation routes to global culture and technology which revolves around the progress of information systems and communication. inspiration that moves us to innovate, to make mistakes and correct them.why the information age is creativity.Creativity is a competitive advantage of business English and modern houses. to change attitudes toward open to new projects that facilitate the transformation and to the challenge of "going global". Inspiration to measure and produce constructive thinking to help us define new goals salon by the desire to create and share knowledge.